Investigation of the high thermal ageing resistance of the 2219 aluminium alloy - Thomas Perrin; Arthur Després; Pierre Heugue; Alexis Deschamps; Frédéric De Geuser (Materials & Design, 2025)
The 2219 aluminium alloy is widely used in high-temperature applications, particularly in aerospace. Thermal ageing during duty can lead to the coarsening of θ’ hardening precipitates, which are responsible for the mechanical properties of the alloy. In this study, temperature gradient heat treatments were employed to evaluate its resistance to thermal ageing over a continuous temperature range of 165 °C to 245 °C for up to 10,000 h. Despite its composition being primarily that of an Al-Cu binary alloy, hardness mappings revealed a limited decrease in mechanical properties. Microstructural characterisation using high-throughput scattering techniques (SAXS & WAXS) showed that this stability is due to a remarkable resistance of the θ’ precipitates to coarsening and limited θ’ to θ transformation, as validated by a precipitate hardening model. This stability suggests that minor alloying elements play a crucial role in thermal resistance. Atom probe tomography (APT) analyses showed that this stability may arise from mechanisms similar to those observed in recently developed ACMZ alloys, as Mn segregations were observed at the interfaces of the θ’ precipitates. However, unlike ACMZ alloys, at 300 °C, the stabilising mechanism is insufficient to preserve mechanical properties, suggesting a strong sensitivity of these mechanisms to compositional variations.